ANALYSIS OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE NASARI SAVING AND LOAN COOPERATIVE IN LHOKSEUMAWE - Anissa, Farah; salsabilla, Cut; Nuryana, Nuryana; Nur Ilham, Rico; Sinta, Irada (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of this study was to determine the level of work discipline in the activities of Nasari Savings and Loans Cooperative Employees. This research is qualitative research using descriptive techniques. Data collection through interviews, observation and documentation at the Nasari Lhokseumawe Savings and Loans Cooperative. The results of this study indicate that at the level of work discipline, the number of employees in construction companies is still small, which has an impact on the low quality of human resource work. The reasons are several things. Examples of low employee discipline include lack of discipline for being late to work, lack of awareness of discipline, and efforts to increase employee efficiency. To overcome this, companies must set an example of discipline for their employees and reward disciplined employees. Keywords: Discipline, work discipline, employee performance Abstract The purpose of this study is to determine the level of work discipline activities of Employees of the Nasari Savings and Loans Cooperative. This research is qualitative research with descriptive data collection techniques through interviews, observation and documentation at the Nasari Lhokseumawe Savings and Loans Cooperative. The results of this study indicate that at the level of work discipline, the number of employees in construction companies is still small, which has an impact on the low quality of human resource work. The reasons are several things. Examples of low employee discipline include lack of discipline for being late for work, lack of awareness of discipline, and efforts to increase employee efficiency. To overcome this, the company must provide an example of discipline to its employees and reward disciplined employees. Savings and Loans Nasari Lhokseumawe held Supervise staff to ensure that personal activities do not deviate from plans and goals set by the company.